Systematic expression analysis of m6A RNA methyltransferases in clear cell renal cell carcinoma - Larissa Gundert (Wiley, 2021)
Abstract Objectives To investigate the regulation of the N‐6‐methyladenosine (m6A) methyltransferases METTL3, METTL14, WTAP, KIAA1429, and METTL4, referred to as “m6A writers,” in clear cell renal cell carcinoma (ccRCC), and other RCC subtypes in respect of the potential prognostic value. Patients and methods Tissue samples were collected within the framework of the Biobank at the Center for Integrated Oncology Bonn. The expression of the methyltransferases was systematically determined in clear cell renal carcinoma (ccRCC) on the RNA (real‐time PCR) and protein level (immunohistochemistry). Additionally, protein expression of the m6A writers was further investigated in papillary RCC, chromophobe RCC, sarcomatoid RCC, oncocytoma, and normal renal tissue (immunohistochemistry). Results The expression of all m6A‐methyltransferases was significantly downregulated in ccRCC compared to benign renal tissue. Low m6A‐methyltransferase levels were correlated with higher histological grade, advanced pT‐stage, pN‐stage, and metastatic disease. Reduced m6A‐methyltransferase expression was associated with shorter overall survival. Conclusion In conclusion, m6A‐methyltransferases are dysregulated in ccRCC and might act as tumor suppressor genes, which could be of particular importance for future diagnostic and therapeutic options.